2016
DOI: 10.1016/j.jhevol.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor pattern fails to predict foramen magnum angle in rodents, strepsirrhine primates, and marsupials

Abstract: Foramen magnum position has traditionally been used as an indicator of bipedality because it has been thought to favor a more "balanced" skull position. Here, we analyzed foramen magnum angle (FMA) in relation to locomotion in three mammalian orders that include bipedal or orthograde species in addition to quadrupedal or pronograde species. In marsupials and strepsirrhine primates, we found that there is no relationship between locomotor pattern and FMA. In rodents, we found that there is a significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 43 publications
4
29
1
1
Order By: Relevance
“…Russo and Kirk () responded to these critiques by Ruth et al . () using an expanded data set, and demonstrated that in fact brain size (i.e., encephalization quotient) had no discernible effect on either FMP or FMO, and that the relationship between FMP and FMO was weak or nonexistent within the mammalian clades they (and Ruth et al, ) examined (rodents, marsupials, primates).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Russo and Kirk () responded to these critiques by Ruth et al . () using an expanded data set, and demonstrated that in fact brain size (i.e., encephalization quotient) had no discernible effect on either FMP or FMO, and that the relationship between FMP and FMO was weak or nonexistent within the mammalian clades they (and Ruth et al, ) examined (rodents, marsupials, primates).…”
Section: Discussionmentioning
confidence: 95%
“…Many researchers accept that the relatively anterior position of the foramen magnum in humans (compared to other extant apes) is likely an adaptation for maintaining balance of the head atop a vertical neck during bipedalism and/or the assumption of orthograde trunk postures (Topinard, ; Dart, ; White et al, ; Kimbel and Rak, ; Russo and Kirk, , ; Kimbel et al, ). However, that the position as well as orientation of the foramen magnum may be linked to other structural and/or functional systems in the body (e.g., brain expansion and/or reorganization, facial size) has contributed to ongoing debate concerning the functional anatomy of this region (Biegert, , ; Kimbel and Rak, ; Russo and Kirk, , ; Ruth et al, ; Villamil, ). For example, Ruth et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another recent study that also comprised strepsirrhines-i.e., the sister-group of all other extant primates, which includes lemurs and lorisoids such as lorises and galagos -, as well as rodents and marsupials, Ruth et al (2016) tested the usually accepted assumption that the foramen magnum position is an indicator of bipedalism because it is supposed to favor a more "balanced" position of the skull. They examined the connection between the angle of this foramen and locomotion in these three clades including bipedal or orthograde species and quadrupedal or pronograde species.…”
Section: An Overview Of Empirical Etho-eco-morphological Studies Acromentioning
confidence: 99%